Impact of Rolandic Epilepsy on Language, Cognitive, and Behavioral Functioning in Children: A Review - Premchand, Angie; Tops, Wim (Journal of Pediatric Epilepsy, 2018)
The objective of this narrative review was to investigate how the clinical aspects, such as age-at-onset, epilepsy duration, centrotemporal spikes, spike location, and seizure frequency, affect various domains of language, cognition, and behavior in children with benign childhood epilepsy. Data were collected using various research databases, including Wiley Online Library, PubMed Central, Elsevier ClinicalKey, and Springer Complete Journals. Keywords such as “Benign Childhood Epilepsy” or “BECTS and language impairment” were used among other terms. Case reports, meta-analyses, and reviews were excluded. Children with benign childhood epilepsy are mainly impaired in semantic processing (receptive language), working memory, attention/inhibitory control, complex visuospatial skills, and social skills. Functional magnetic resonance imaging reveals not only structural abnormalities, but also alterations in language, sensorimotor, attentional, and social networks, suggesting long-term consequences. It so seems that the occurrence of centrotemporal spikes (with or without seizures), especially at a young age (below 6 years) and for an extended period of time, is the most meaningful contributor to the language, cognitive, and behavioral deficits in benign childhood epilepsy with centrotemporal spikes (BECTS), while the distribution of centrotemporal spikes (left, right, bilateral) seems of only little significance.
Keywords: BECTS; neuropsychological; children